2017
DOI: 10.1002/jcb.26249
|View full text |Cite
|
Sign up to set email alerts
|

Sodium salicylate modulates inflammatory responses through AMP‐activated protein kinase activation in LPS‐stimulated THP‐1 cells

Abstract: Sodium salicylate (NaSal) is a nonsteroidal anti‐inflammatory drug. The putative mechanisms for NaSal's pharmacologic actions include the inhibition of cyclooxygenases, platelet‐derived thromboxane A2, and NF‐κB signaling. Recent studies demonstrated that salicylate could activate AMP‐activated protein kinase (AMPK), an energy sensor that maintains the balance between ATP production and consumption. The anti‐inflammatory action of AMPK has been reported to be mediated by promoting mitochondrial biogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…To further investigate the mechanisms of nuciferine on anti-inflammatory effect, the degradation of IκB-α protein levels were determined with exposure to the nuciferine in the LPS-treated RAW 264.7 cells ( Figure 5 , original results see Figure S2 ). When stimulated only with LPS, the cytosolic IκB-α protein was markedly degraded, consistent with the THP-1 treatment results [ 17 ]. However, nuciferine treatment attenuated the pro-inflammatory effect of the LPS.…”
Section: Resultssupporting
confidence: 83%
“…To further investigate the mechanisms of nuciferine on anti-inflammatory effect, the degradation of IκB-α protein levels were determined with exposure to the nuciferine in the LPS-treated RAW 264.7 cells ( Figure 5 , original results see Figure S2 ). When stimulated only with LPS, the cytosolic IκB-α protein was markedly degraded, consistent with the THP-1 treatment results [ 17 ]. However, nuciferine treatment attenuated the pro-inflammatory effect of the LPS.…”
Section: Resultssupporting
confidence: 83%
“…How does this relationship affect inflammation? Our data showed that AMPK activation not only played an anti-inflammatory role in LPS-induced inflammation ( Figure S1A), as we previously mentioned (15), but also reduced STAT3 phosphorylation ( Figure S1B), similar to other reports (24,25). In addition, we confirmed the pro-inflammatory impact of STAT3 in LPS-stressed macrophages using genetic and pharmacological approaches ( Figure S2).…”
Section: Resultssupporting
confidence: 91%
“…Although previous studies have revealed that STAT3 phosphorylation increases in LPS-stimulated macrophages (24,25), and AMPK regulates STAT3 deactivation [11,16], the exact role of STAT3 in the AMPK-STAT3 regulatory pathway is ambiguous in endotoxin-mediated inflammation. In this study, we assessed the following issues: (1) the timedependent alterations in STAT3 and AMPK activities during LPS-mediated inflammation; (2) the significance of STAT3 in the anti-inflammatory effect of AMPK; (3).…”
Section: Introductionmentioning
confidence: 98%
“…Monocyte markers associated with a decreased risk of SIV mac251 acquisition included genes implicated in IL-1β production and regulation ( ANXA2 , EIF4A and IL1RL2 ) and in the suppression of proinflammatory cytokines ( TLR10 and TBK1 ) 22,23 . Gene network inference revealed the importance of hypoxia-inducible factor 1-α (HIF1-α) as a key transcriptional regulator of these protective genes 13,14 (Fig.…”
Section: Resultsmentioning
confidence: 99%